(untitled) (Journal of Geography and Environmental Management, 2019)
Scientists around the world drew attention to the increasing frequency of abnormal natural phenomena including climate: droughts, excessive rain, flooding and other periods. This article discusses the features of atmospheric circulation of the northern hemisphere in case of droughts in Kazakhstan.